The Czech Republic science park critical location factor analysis - Čížek, Petr (Univerzita Pardubice, 2015)
The contribution is focused on the critical location factor analysis of science parks in the Czech Republic. The analysis investigates four major critical location factors – Proximity to international airport, Proximity to capital cities, Good road network and Good rail link to capital cities. These factors are applied to the science parks registered at the Science and Technology Parks Association. The results show the dominance of the science parks located near the biggest cities – Prague and Brno. It is mainly because of the excellent access to the highway and international airport for the tenants. However many science parks from other regions performed well, which is mostly consequence of the abovestandard access to the highway. On the other hand for the same reason science parks located apart from highways performed poorly. The contribution contains the results for the all science parks by individual factor or by overall score. The analysis is also focused on the data distribution of the results for better understanding the outcome.
Keywords: critical factors; location analysis; science parks; startups; M13; M21